2010
DOI: 10.1016/j.juro.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor CAG Repeat Length and Association With Prostate Cancer Risk: Results From the Prostate Cancer Prevention Trial

Abstract: PURPOSE We investigated the association between the length of the polymorphic trinucleotide CAG microsatellite repeats in exon 1 of the androgen receptor (AR) gene and the risk of prostate cancer. METHODS This is a nested case-control study of 1159 cases and 1353 controls drawn from the Prostate Cancer Prevention Trial, a randomized, placebo-controlled trial testing whether finasteride, a 5α-reductase inhibitor, could reduce the 7-year period prevalence of prostate cancer. During the course of the PCPT, men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
(27 reference statements)
2
33
0
Order By: Relevance
“…In our cohort of Bulgarian patients and controls the length of the repeats ranged between 14 and 29 to 31, with a peak at 21 repeats and another at 24 repeats ( Figure 2). Our results for CAG repeat polymorphism in AR (Tables 6 and 8) are consistent with some recent studies that did not find any association of this microsatellite with either PC risk (20,21) or with time to progression, overall survival, Gleason score, and clinical stage at diagnosis (22). Conflicting conclusions may be due to differences in design, small sample size in some studies, differences in environment, genetic admixture, ascertainment bias (including diagnosis before or after the age of PSA testing), and differences in tract length cut off points.…”
Section: Arsupporting
confidence: 92%
“…In our cohort of Bulgarian patients and controls the length of the repeats ranged between 14 and 29 to 31, with a peak at 21 repeats and another at 24 repeats ( Figure 2). Our results for CAG repeat polymorphism in AR (Tables 6 and 8) are consistent with some recent studies that did not find any association of this microsatellite with either PC risk (20,21) or with time to progression, overall survival, Gleason score, and clinical stage at diagnosis (22). Conflicting conclusions may be due to differences in design, small sample size in some studies, differences in environment, genetic admixture, ascertainment bias (including diagnosis before or after the age of PSA testing), and differences in tract length cut off points.…”
Section: Arsupporting
confidence: 92%
“…One suggestion that AR plays a causative role in tumorigenesis comes from studies demonstrating an association between CAG repeat length, which influences AR activity, and the risk of prostate cancer (PC); however, other studies contradict these findings (Bosland 2000, Nelson et al 2003, Lindstrom et al 2010, Price et al 2010. Two studies of genetically modified mice suggest that AR plays a role in cancer initiation.…”
Section: Ar In Prostate Cancer Initiationmentioning
confidence: 99%
“…Epidemiological studies initially found association between fewer CAG repeats and increased risk or more aggressive disease (e.g., (Irvine et al, 1995;Giovannucci et al, 1997;Stanford et al, 1997)). However results vary with ethnic group and most recent studies find no association with risk (e.g., (Lindstrom et al, 2010;Price et al, 2010)). Conflicting conclusions stem from many aspects of study design, including small sample sizes, differences in environment, genetic admixture, ascertainment bias (including diagnosis before or after the age of PSA testing) and differences in tract length cut-off points.…”
Section: Human Genetic and Genomic Studies Of The Cag Repeat And Prosmentioning
confidence: 92%